2015
DOI: 10.1145/2764464
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Networking Solutions in Cloud-Based Environments

Abstract: The energy consumed by data centers hosting cloud services is increasing enormously. This brings the need to reduce energy consumption of different components in data centers. In this work, we focus on energy efficiency of the networking component. However, how different networking solutions impact energy consumption is still an open question. We investigate the state of the art in energy-efficient networking solutions in cloud-based environments. We follow a systematic literature review method to select prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In the research literature, there are extensive surveys from slightly different points of view that cover approaches related to green networking [4,27,37,128,129].…”
Section: A Existing Classification Of Green Networking Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research literature, there are extensive surveys from slightly different points of view that cover approaches related to green networking [4,27,37,128,129].…”
Section: A Existing Classification Of Green Networking Approachesmentioning
confidence: 99%
“…Finally, sleeping/standby is founded on power management basics that allow network equipment (or parts of them) to be switched off, to enter very low power states. A recent survey [128] mainly focuses on energy efficient solutions for cloud-based networking components, making use of the system literature review (SLR) research method [129]. Four groups of methodologies have been identified based on the networking component granularity: (i) Data Center (DC) layer, (ii) Application (App) layer, (iii) Network layer, and (iv) Device layer.…”
Section: A Existing Classification Of Green Networking Approachesmentioning
confidence: 99%
“…Measuring VMs and containers is quite difficult as resources are not equally shared [43]. Many clouds use oversubscription, whereby resources are over promised to many services with the hope that these services do not need all of these resources at the same time.…”
Section: Virtualizationmentioning
confidence: 99%
“…Currently there is some work on attributing energy consumption to virtualized machines [44], [43], but it is just the beginning of such research. Little to no work has been done to estimate the energy use of services within containers such as docker.…”
Section: Virtualizationmentioning
confidence: 99%
“…Given SDNs wide range of applications and their rapid growth in data center networks, they are often chosen as part of the power efficient solutions. In an earlier systematic literature review [3], we studied the existing energy efficient networking solutions and we observed a growing trend in using SDNs combined with energy awareness. The existing energy efficient networking solutions are implemented as flow schedulers that fullfill user-defined quality requirements while considering energy consumption improvements.…”
Section: Introductionmentioning
confidence: 99%